Do bedside whiteboards enhance communication in hospitals? An exploratory multimethod study of patient and nurse perspectives. Issue 10 (6th November 2019) - Goyal, Anupama; Glanzman, Hanna; Quinn, Martha; Tur, Komalpreet; Singh, Sweta; Winter, Suzanne; Snyder, Ashley; Chopra, Vineet
Abstract : Objective: To understand patient and nurse views on usability, design, content, barriers and facilitators of hospital whiteboard utilisation in patient rooms. Design: Multimethods study. Setting: Adult medical-surgical units at a quaternary care academic centre. Participants: Four hundred and thirty-eight adult patients admitted to inpatient units participated in bedside surveys. Two focus groups with a total of 13 nurses responsible for updating and maintaining the whiteboards were conducted. Results: Most survey respondents were male (55%), ≥51 years of age (69%) and admitted to the hospital ≤4 times in the past 12 months (90%). Over 95% of patients found the whiteboard helpful and 92% read the information on the whiteboard frequently. Patients stated that nurses, not doctors, were the most frequent user of whiteboards (93% vs 9.4%, p<0.001, respectively). Patients indicated that the name of the team members (95%), current date (87%), upcoming tests/procedures (80%) and goals of care (63%) were most useful. While 60% of patients were aware that they could use the whiteboard for questions/comments for providers, those with ≥5 admissions in the past 12 months were significantly more likely to be aware of this aspect (p<0.001). In focus groups, nurses reported they maintained the content on the boards and cited lack of access to clinical information and limited use by doctors as barriers. Nurses suggested creating a curriculum to orient patients to whiteboards on admission, and educational programmes for physicians to increase whiteboard utilisation. Conclusion: Bedside whiteboards are highly prevalent in hospitals. Orienting patients and their families to their purpose, encouraging daily use of the medium and nurse–physician engagement around this tool may help facilitate communication and information sharing.